Enterprise Architecture Model for Smart Government Implementation - Lestari, Merryana; Wijaya, Agustinus Fritz; Chandra, Michelle Mei Diana (Journal of Information System and Informatics, 2025)
This research aims to develop an enterprise architecture (EA) model to support the implementation of Smart Government that utilizes information and communication technology (ICT) to enhance efficiency, transparency, and public participation in governmental processes. The development of this EA model adopts a holistic approach, integrating various components of technology, organization, and business processes within the context of government to provide guidance for government agencies in planning, implementing, and managing the digital transformation required to achieve Smart Government. The findings of this study indicate that the proposed enterprise architecture model offers a clear and flexible structure to support the integration of government agencies, public service providers, and citizens. It is expected that by utilizing this EA model, governments can improve public services, operational efficiency, and create a more transparent and accountable environment. By leveraging this EA model, government agencies can streamline processes, enhance decision-making through data-driven insights, and foster greater inter-agency collaboration. It is expected that this model will improve public sector services by increasing accessibility, reducing administrative burdens, and optimizing resource utilization. Furthermore, the adoption of this model is anticipated to accelerate the digital transformation of the public sector, driving significant improvements in government service delivery, responsiveness, and citizen engagement.